Deletion of exon 4 in LAMA2 is the most frequent mutation in Chinese patients with laminin α2-related muscular dystrophy. Issue 1 (December 2018) - Ge, Lin; Liu, Aijie; Gao, Kai; Du, Renqian; Ding, Juan; Mao, Bing; Hua, Ying; Zhang, Xiaoli; Tan, Dandan; Yang, Haipo; Fu, Xiaona; Fan, Yanbin; et al.
Abstract Although recessive mutations inLAMA2 are already known to cause laminin α2-related muscular dystrophy, a rare neuromuscular disorder, large deletions or duplications within this gene are not well-characterized. In this study, we applied next-generation sequencing-based copy number variation profiling in 114 individuals clinically diagnosed with laminin α2-related muscular dystrophy, including 96 who harbouredLAMA2 mutations and 34 who harboured intragenic rearrangements. In total, we detected 18 distinctLAMA2 copy number variations that have been reported only among Chinese, 10 of which are novel. The frequency of CNVs in the cohort was 19.3%. Deletion of exon 4 was detected in 10 alleles of eight patients, accounting for 27% of all copy number variations. These patients are Han Chinese and were found to have the same haplotype and sequence at the breakpoint junction, suggesting that exon 4 deletion is a founder mutation in Chinese Han and a mutation hotspot. Moreover, the data highlight our approach, a modified next-generation sequencing assay, as a robust and sensitive tool to detectLAMA2 variants; the assay identifies 85.7% of breakpoint junctions directly alongside sequence information. The method can be applied to clinical samples to determine causal variants underlying various Mendelian disorders.